ANALISIS PROGRAM PADHANGE ATI DI JTV SURABAYA PERSPEKTIF DAKWAH ISLAM - Wassamatul Hikmah; Yohandi; Nurul Abrari (Maddah : Jurnal Komunikasi dan Konseling Islam, 2026)
This study examines the "Padhange Ati" program a social and religious initiative from the perspective of Islamic da'wah (preaching/mission). The program aims to enhance the spiritual and moral quality of the community through activities such as religious study sessions, social service, and skills development. The researcher’s objectives are to analyze the "Padhange Ati" program process at JTV Surabaya from an Islamic da'wah perspective and to identify the extent to which Islamic da'wah principles are applied within the program's operations. A descriptive qualitative research method with a case study approach was employed. The results indicate that the production process of "Padhange Ati" follows three stages in accordance with Standard Operating Procedures (SOP): pre-production, production, and post-production. The program incorporates Islamic da'wah concepts packaged within a talk show format. This talk show format facilitates the delivery of content and Q&A sessions between resource persons and the audience, integrating the principles of bil-hikmah (wisdom), mau'izhatil-hasanah (good counsel), and mujadalah billati hiya ahsan (reasoning in the best manner).